FeTe diatomic catalyst and method for preparing the same

CN116344845BActive Publication Date: 2026-10-27CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211395342.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-09
Publication Date
2026-10-27
Estimated Expiration
2042-11-09

AI Technical Summary

Technical Problem

但是,上述方法存在以下问题,(1)DACs与SACs普遍共存;(2)碳载SACs在制备过程中,碳载体容易团聚,造成孔的堵塞,降低了传质效率

Benefits of technology

[0051](1)本发明基于一种FeTe双原子催化剂及其制备方法呈菱形十二面体结构,平均粒径为300~500nm,其中,所述铁单原子以原子级均匀分布于碳多面体中;;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003933196660000011
    Figure HDA0003933196660000011
  • Figure HDA0003933196660000012
    Figure HDA0003933196660000012
  • Figure HDA0003933196660000021
    Figure HDA0003933196660000021
Patent Text Reader

Abstract

The application discloses an FeTe diatomic catalyst and a preparation method thereof, and belongs to the field of electrochemistry.The FeTe diatomic catalyst has a rhombic dodecahedron structure, and iron and tellurium diatoms are uniformly distributed in the rhombic dodecahedron nitrogen-doped carbon at an atomic level.The application further discloses a preparation method of the FeTe diatomic catalyst.The FeTe diatomic catalyst can efficiently catalyze an oxygen electro-reduction reaction, and when assembled into a zinc-air battery, the whole battery can have a current density of 50 mA cm ‑2 The performance is far superior to that of a commercial Pt / C+RuO2 after 400 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a catalyst, specifically to an FeTe diatomic catalyst and its preparation method. Background Technology

[0002] Single-atom catalysts (SACs) have become a frontier in catalysis science in recent years. Reducing active species from the nanoscale to the atomic level is an effective strategy to improve catalytic performance. On the one hand, theoretically, it is possible to achieve 100% atomic utilization, fully expose catalytic active sites, and increase the number of active sites. On the other hand, it is possible to improve the intrinsic activity of reactive sites through strong interactions and charge transfer effects between metal single-atom active centers and supports. However, single-atom catalysts with M-N4 sites, represented by metal atoms and nitrogen coordination, still suffer from problems such as insufficient reactivity and poor stability. Further modification and regulation of single-atom catalysts are needed. Currently, effective regulation strategies can be roughly divided into four categories: (1) increasing the loading of single-atom Fe; (2) increasing the specific surface area to expose more active sites; (3) introducing auxiliary components such as FeCo alloys and Fe3C; and (4) local doping of heteroatoms.

[0003] The development of next-generation energy conversion and storage devices, such as fuel cells and metal-air batteries, heavily relies on electrocatalytic oxygen reduction reactions (ORR). Noble metal-based ORR catalysts, primarily platinum (Pt) electrocatalysts, have seen significant development and exhibit high activity. However, their high cost, scarce reserves, and long-term stability issues severely hinder large-scale commercial applications. Iron / nitrogen-doped carbon (Fe / NC) catalysts have emerged as promising next-generation catalytic materials to replace noble metals in recent years. Despite the rapid development of Fe-based ORR catalysts, especially single-atom iron catalysts, the performance of these materials still falls short of application requirements.

[0004] To address these issues, reducing the active species of catalysts from particles to the atomic scale is an effective strategy for improving catalyst performance. At the same time, designing diatomic catalysts (DACs) at the atomic scale not only compensates for the low loading of SACs, but also enhances the intrinsic activity of active sites by utilizing the strong interaction between diatoms and the support. Furthermore, the synergistic effect between metal diatoms has a significant auxiliary advantage in breaking O-O bonds.

[0005] Xing et al. disclosed an iron-cobalt diatomic catalyst whose oxygen reduction performance was 20 times that of a single-atom catalyst (Climbing the Apex of the ORR Volcano Plot via Binuclear Site Construction: Electronic and Geometric Engineering, J. Am. Chem. Soc. 2019, 44, 17763-1777); Sun et al. prepared a Pt-Ru diatomic catalyst by atomic deposition, which showed high hydrogen evolution mass activity and stability (Atomic layer deposited Pt-Ru dual-metal dimers and identifying their active sites for hydrogen evolution reaction. Nature Communications. 2019,10, 4936). However, the above methods have the following problems: (1) DACs and SACs generally coexist; (2) during the preparation of carbon-supported SACs, the carbon support is prone to agglomeration, causing pore blockage and reducing mass transfer efficiency. Both of these hinder the further improvement of the ORR performance of DACs.

[0006] Therefore, there is an urgent need to develop a method for preparing a diatomic catalyst that has good atomic-level dispersion, excellent electrocatalytic oxygen reduction performance, superior cycle performance compared to commercial Pt / C catalysts, and is simple, efficient, low-cost, versatile, and suitable for industrial production. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a zinc-air battery that can efficiently catalyze ORR and whose performance is superior to commercial Pt / C and other noble metal-based catalysts.

[0008] The further technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art, fill the gap of tellurium-iron diatomic catalysts, and provide a method for synthesizing tellurium-doped iron single-atom carbon polyhedral catalysts that is simple, efficient, low-cost, versatile, and suitable for industrial production.

[0009] The technical solution adopted to address the above problems is as follows: Based on a FeTe diatomic catalyst and its preparation method, the tellurium-iron diatomic carbon polyhedron catalyst is a catalyst with a rhombic dodecahedral structure, wherein iron and tellurium atoms are uniformly distributed in the carbon polyhedron in the form of atomic pairs;

[0010] The invention's approach is based on the principle that ORR generally follows a 2-electron or 4-electron catalytic pathway. Compared to non-Fe-based SACs, Fe-based SACs exhibit higher ORR catalytic activity and stability, and a reaction process approaching 4 electrons. Preparing highly active and stable iron single-atom catalysts on nitrogen-doped carbon supports yields excellent ORR catalytic activity; this process utilizes a host-guest strategy and high-temperature heat treatment. Through the reaction of a strong reducing agent with sodium tellurite, sodium tellurite is reduced to the corresponding negatively charged anion (Te2). 2- ), and Te 2- Iron readily bonds with single iron atoms to form a stable FeTe diatomic catalyst. This invention synthesizes FeTe diatomic catalysts via a hydrothermal method, where the iron single atoms are anchored by nitrogen and carbon atoms (Fe-NC), and tellurium atoms are coordinated with the iron single atoms, existing as iron-tellurium diatomic pairs. The FeTe diatomic catalyst has an overall rhombic dodecahedral structure. This structure exposes more catalytic ORR active sites, and the well-developed internal pores facilitate the coordination of tellurium atoms with iron single atoms during synthesis, further enhancing ORR catalytic activity.

[0011] Preferably, the amount of N doping in the catalyst is 0.01 to 1.00%, which is more conducive to anchoring iron single atoms.

[0012] Preferably, the mass percentage of iron in the catalyst is 0.01 to 5.00%, which can prevent the aggregation of iron single atoms in the carbon polyhedron.

[0013] Preferably, the mass percentage of tellurium in the catalyst is 0.01 to 3.00%, which can enhance ORR activity without forming metal tellurium compounds that would weaken ORR reaction activity.

[0014] Preferably, the average particle size of the catalyst is 200–500 nm, which is beneficial for exposing more bifunctional reactive sites and for the adsorption and desorption of reaction intermediates.

[0015] Preferably, elemental tellurium includes tellurium powder; the salt containing tellurium includes one or more of sodium tellurite and sodium tellurate. More preferably, the salt containing tellurium is sodium tellurite, which is easily reduced to a negatively charged anion by a strong reducing agent.

[0016] The technical solution adopted by this invention to further solve its technical problem is as follows: A method for preparing a FeTe diatomic catalyst, comprising the following steps:

[0017] (1) First, the metal salt and zinc nitrate are stirred and dissolved in methanol solvent to obtain solution A. Then, the N-containing organic ligand is stirred and dissolved in methanol solvent to obtain solution B. After stirring and mixing solutions A and B, the mixture is allowed to stand for aging, centrifuged, filtered and washed, and vacuum dried to obtain precursor powder.

[0018] (2) The precursor powder obtained in step (1) is subjected to a heat treatment under an inert atmosphere and cooled in the furnace to obtain a black powder; the temperature of the heat treatment is 600℃~1000℃.

[0019] (3) Dissolve the strong reducing agent in deoxygenated ultrapure water until the solution is clear and transparent to obtain solution C. Add elemental tellurium or a salt containing tellurium to solution C and shake until the solution is clear again to obtain precursor solution D.

[0020] (4) Add the black powder obtained in step (2) to the precursor solution D obtained in step (3), disperse by ultrasonication, perform hydrothermal reaction, centrifuge, filter and wash, and freeze dry to obtain sample powder; the mass-volume ratio of the black powder to elemental tellurium or salt containing tellurium element is 0.1g:1mL~10mL; the molar concentration of the iron salt solution is 0.05~0.50mol / L;

[0021] (5) Under the protection of an inert atmosphere, the sample powder obtained in step (4) is subjected to a second heat treatment and cooled in the furnace to obtain the FeTe diatomic catalyst; the temperature of the second heat treatment is 300℃~600℃.

[0022] Preferably, in step (1), the mass ratio of the iron salt to zinc nitrate is 1:8 to 50 (more preferably 1:10 to 30). Zinc ions, acting as metal nodes, form molecular cages through chemical coordination with nitrogen-containing organic ligands. The metal salt, as a guest molecule, is encapsulated within the cavity of the molecular cage. The metal salt, zinc nitrate, and nitrogen-containing organic ligands form a metal-organic framework (MOF), which has a highly controllable metal component ratio, facilitating the dispersion of metal atoms and preventing their aggregation during pyrolysis. Zn is a fundamental element constituting the metal-organic framework. Limiting the mass ratio of the metal salt to zinc nitrate to the range of 1:8 to 50 is to prevent excessive metal aggregation, avoiding the formation of corresponding metal oxides, metal carbides, or metal nanoparticles, which would reduce the utilization rate of metal atoms and consequently decrease electrochemical activity.

[0023] Preferably, in solution A of step (1), the mass-to-volume ratio (g / mL) of the sum of the iron salt and zinc nitrate to the methanol solvent is 1:20 to 200 (more preferably 1:25 to 100). If the amount of methanol solvent is too small, the size of the MOF will be too large; if the amount of methanol solvent is too large, the yield of the product will be greatly reduced.

[0024] Preferably, in step (1), the iron salt includes one or more of iron carbonyl, iron acetylacetone, iron acetate, iron chloride, iron sulfate, or iron nitrate.

[0025] Preferably, in step (1), the mass ratio of zinc nitrate to nitrogen-containing organic ligand is 1:0.6–3.0 (more preferably 1:0.8–2.0). The nitrogen-containing organic ligand mainly provides a precursor containing both C and N, which coordinates with the metal salt to form a regular polyhedral morphology. If too much nitrogen-containing organic ligand is used, the size of the MOF will be too large; if too little nitrogen-containing organic ligand is used, the product yield will be significantly reduced.

[0026] Preferably, in solution B of step (1), the mass-to-volume ratio (g / mL) of the N-containing organic ligand to the methanol solvent is 1:20 to 200 (more preferably 1:21 to 100). If the amount of methanol solvent is too small, the size of the MOF will be too large; if the amount of methanol solvent is too large, the yield of the product will be greatly reduced.

[0027] Preferably, in step (1), the N-containing organic ligand includes one or more of dimethylimidazole, hexamethylenetetramine, or ethylenediaminetetraacetic acid.

[0028] Preferably, in step (1), the stirring and dissolving temperature is room temperature and the time is 10 to 30 minutes.

[0029] Preferably, in step (1), the stirring and mixing temperature is room temperature to 140°C, and the time is 1 to 6 hours.

[0030] Preferably, in step (1), the static aging temperature is room temperature to 140°C, and the time is 6 to 24 hours. The static aging is to allow the metal salt to undergo complete chemical coordination with the nitrogen-containing organic ligand to obtain Zn. 2+ Complexes containing N-containing organic ligands.

[0031] Preferably, in step (1), the vacuum drying pressure is 0.05~0.5MPa and the time is 12~72h.

[0032] Preferably, in step (1), the filtration and washing refers to filtering and washing the precipitate ≥2 times with N,N-dimethylformamide and methanol respectively. The resulting precipitate is first washed with N,N-dimethylformamide (DMF), and then with methanol. The purpose is to better dissolve any unreacted metal salts in DMF, while methanol can effectively dissolve residual DMF in the precipitate. Since methanol has a very low boiling point, it can escape from the sample after vacuum drying, avoiding the influence of the organic solvents DMF and methanol on the sample. This invention's method, through a two-step organic solvent washing process, provides MOF-derived carbon supports with a high specific surface area, large porosity, and a three-dimensional interconnected pore structure, which facilitates the full exposure of metal active sites.

[0033] Preferably, in step (2), the duration of the first heat treatment is 1–6 hours. During the heat treatment, the N-containing organic ligands decompose, generating N-doped C polyhedra in situ, and iron atoms coordinate with the doped N atoms; simultaneously, Zn volatilizes, resulting in the formation of numerous micropores. After the first heat treatment, the MOF can undergo complete transformation. The inert atmosphere is a mixture of nitrogen, argon, and a gas with a volume fraction of 5% H2 / 95% N2, or a gas with a volume fraction of 5% H2 / 95% Ar.

[0034] Preferably, the deoxygenated ultrapure water in step (3) is produced by introducing an inert gas, such as argon or nitrogen, into the ultrapure water. More preferably, argon is introduced to remove dissolved oxygen from the ultrapure water and prevent dissolved oxygen from oxidizing Te. 2- .

[0035] Preferably, the strong reducing agent in step (3) includes one or more of sodium borohydride or hydrazine hydrate. More preferably, the strong reducing agent is an aqueous solution of hydrazine hydrate with a mass fraction of 80%.

[0036] Preferably, the tellurium element in step (3) includes tellurium powder, and the tellurium-containing salt includes one or more of sodium tellurite and sodium tellurate. More preferably, the tellurium-containing salt is sodium tellurite. Compared to other methods, using hydrazine hydrate to directly reduce sodium tellurite in an aqueous solution can efficiently and rapidly synthesize Te. 2- .

[0037] Preferably, in step (3), the oscillation temperature is 20-40℃ and the oscillation time is 10-30 min; the concentration of the strong reducing agent in solution C is 1-4 mol / L.

[0038] Preferably, in step (3), the concentration of elemental tellurium or salt containing tellurium in solution D is 0.05~0.50 mol / L.

[0039] Preferably, in step (3), the molar ratio of the strong reducing agent to elemental tellurium is 2 to 80:1, or the molar ratio of the strong reducing agent to a salt containing tellurium is 2 to 80:1.

[0040] Preferably, in step (4), the filtration and washing refers to filtering and washing the precipitate ≥2 times with water and ethanol respectively.

[0041] Preferably, in step (4), the hydrothermal reaction temperature is 160–220°C, and the time is 12–48 h. During the hydrothermal treatment, Te 2- It will bond with exposed iron single atoms on the surface to form iron-tellurium atom pairs.

[0042] Preferably, in step (4), the centrifugation speed is 6000~10000 r / min and the centrifugation time is 1.5~5 min.

[0043] Preferably, in step (4), the freeze-drying temperature is -10 to -30°C, and the time is 12 to 72 hours. Under the freeze-drying conditions, moisture can be removed from the frozen sample, and its morphology can be well maintained without agglomeration or collapse.

[0044] Preferably, in step (4), the time for the secondary heat treatment is 1 to 6 hours to prevent the agglomeration of iron single atoms due to excessively high annealing temperature and excessively long holding time.

[0045] Preferably, in step (4), the inert atmosphere is a mixture of nitrogen, argon, and a mixture of 5% H2 / 95% N2 by volume, or a mixture of 5% H2 / 95% Ar by volume.

[0046] Preferably, in step (1), the centrifugation speed is 4000-10000 r / min and the time is 0.5-10 min.

[0047] Preferably, in step (1), the vacuum drying temperature is room temperature to 80°C, the pressure is 0.05 to 0.5 MPa, and the time is 12 to 72 h.

[0048] A FeTe diatomic catalyst was prepared by any of the methods described above.

[0049] Application of a FeTe diatomic catalyst as described above in ORR catalytic reaction.

[0050] The beneficial effects of this invention are as follows:

[0051] (1) The present invention is based on a FeTe diatomic catalyst and its preparation method, which has a rhombic dodecahedral structure with an average particle size of 300-500 nm, wherein the iron single atoms are uniformly distributed in the carbon polyhedron at the atomic level;

[0052] (2) Based on a FeTe diatomic catalyst and its preparation method, the present invention exhibits high half-wave potential (0.946V) and high durability in alkaline medium (0.1 mol / LKOH). After 10,000 cycles of cyclic voltammetry acceleration, the half-wave potential is almost lost. It can be used as a highly efficient ORR electrocatalyst to replace Pt / C noble metal catalysts in alkaline medium.

[0053] (3) Based on a FeTe diatomic catalyst and its preparation method, this invention is assembled into a quasi-solid-state zinc-air battery, which operates at 50 mA cm⁻¹. -2 At a current density of 435 cycles, it can stably cycle for 435 cycles, which is much higher than the cycle number of commercial Pt / C+Ir / C catalysts, demonstrating good high-current cycling performance.

[0054] (4) The synthesis process of the present invention is simple, efficient, low-cost, versatile and suitable for industrial production. Attached Figure Description

[0055] Figure 1 This is a SEM image of the FeTe-DAC from Embodiment 1 of the present invention;

[0056] Figure 2 This is a TEM image of the FeTe-DAC from Embodiment 1 of the present invention;

[0057] Figure 3 This is the XRD pattern of the FeTe-DAC in Embodiment 1 of the present invention;

[0058] Figure 4 This is the AC-HAADF-STEM image of the FeTe-DAC in Embodiment 1 of the present invention;

[0059] Figure 5 This is a nitrogen adsorption / desorption curve of FeTe-DAC in Example 1 of the present invention;

[0060] Figure 6 This is the N 1s XPS spectrum of the FeTe-DAC in Embodiment 1 of the present invention;

[0061] Figure 7 This is the Fe 2p XPS spectrum of FeTe-DAC in Example 1 of the present invention;

[0062] Figure 8 This is the Te 3d XPS spectrum of the FeTe-DAC in Embodiment 1 of the present invention;

[0063] Figure 9 This is the LSV curve of the electrocatalytic oxygen reduction reaction of FeTe-DAC and noble metal catalyst Pt / C in 0.1 mol / L KOH in Example 1 of the present invention;

[0064] Figure 10 This is the LSV curve of the electrocatalytic oxygen reduction reaction of FeTe-DAC at different rotation speeds in Example 1 of the present invention;

[0065] Figure 11 This is the LSV stability curve of FeTe-DAC in Example 1 of the present invention before and after 10,000 CV cycles in 0.1 mol / L KOH for electrocatalytic oxygen reduction reaction;

[0066] Figure 12 This is the cycle performance of FeTe-DAC and Pt / C noble metal catalysts in a quasi-solid-state zinc-air battery according to Example 1 of the present invention;

[0067] Figure 13This is the LSV curve of the electrocatalytic oxygen reduction reaction of FeTe-DAC and Pt / C noble metal catalysts in 0.1 mol / L KOH in Example 2 of the present invention;

[0068] Figure 14 This is the LSV curve of the electrocatalytic oxygen reduction reaction of FeTe-DAC and Pt / C noble metal catalysts in 0.1 mol / L KOH in Example 3 of the present invention;

[0069] Figure 15 The Te 3d XPS spectrum of the sample obtained in Comparative Example 4 is shown below.

[0070] Figure 16 The LSV stability curves of the sample obtained in Comparative Example 4 before and after 10,000 CV cycles in 0.1 mol / L KOH for the electrocatalytic oxygen reduction reaction are shown. Detailed Implementation

[0071] The present invention will be further described below with reference to the embodiments and accompanying drawings.

[0072] The protective atmosphere used in the embodiments of this invention is a high-purity atmosphere with a purity of ≥99.9%. Unless otherwise specified, the raw materials or chemical reagents used in the embodiments of this invention are obtained through conventional commercial channels.

[0073] Example 1 based on FeTe diatomic catalyst

[0074] The FeTe-based diatomic catalyst (denoted as FeTe-DAC) is a catalyst with a rhombic dodecahedral structure, wherein the iron single atoms and tellurium atoms are uniformly distributed in the carbon polyhedron in the form of atomic pairs (diatoms); the N doping amount in FeTe-DAC is 0.35%; the mass percentage of the iron single atoms in FeTe-DAC is 1.46%; the mass percentage of the tellurium element in FeTe-DAC is 0.62%; and the average particle size of FeTe-DAC is 378 nm.

[0075] (1) First, 150 mg of iron acetylacetone and 1190 mg of zinc nitrate were dissolved in 30 mL of methanol solvent at room temperature for 15 min to obtain solution A. Then, 1314 mg of dimethylimidazole was dissolved in 30 mL of methanol solvent at room temperature for 15 min to obtain solution B. Then, solution A and solution B were mixed at room temperature for 15 min and allowed to stand for 12 h. After that, the mixture was centrifuged at 7500 r / min for 3 min. The precipitate was washed three times by filtering with N,N-dimethylacetamide and methanol. The mixture was then vacuum dried at 25 ℃ and 0.05~0.5 MPa for 8 h to obtain precursor powder.

[0076] (2) The precursor powder obtained in step (1) was heated to 900°C at a rate of 5°C / min under the protection of high-purity nitrogen atmosphere, held for 3h, and subjected to a single annealing heat treatment. The powder was then cooled in the furnace to obtain 50 mg of black powder SA-Fe / NC.

[0077] (3) 110.8 mg of sodium tellurite was added to solution C, which was prepared by 2 mL of deoxygenated ultrapure water using hydrazine aqueous solution (151.3 mg, 0.005 mol). The solution was gently shaken at 25 °C for 30 min until the solution became clear, thus obtaining precursor solution D.

[0078] (4) The black powder SA-Fe / NC obtained in step (2) was ultrasonically dispersed in the precursor solution D obtained in step (3), and hydrothermally reacted at 200℃ for 24h. After centrifugation at 9000 r / min for 3 min, the precipitate was washed three times with deoxygenated ultrapure water and ethanol, and then freeze-dried at -35℃ for 24h.

[0079] (5) The powder obtained in step (4) is heated to 500°C at a rate of 5°C / min under a high-purity nitrogen atmosphere and held for 1 hour for a second annealing heat treatment. It is then cooled in the furnace to obtain FeTe-DAC.

[0080] like Figure 1 As shown, the FeTe-DAC in this embodiment of the invention has a rhombic dodecahedral structure and is well dispersed without agglomeration.

[0081] like Figure 2 As shown, the FeTe-DAC in this embodiment of the invention has a rhombic dodecahedral structure and is well dispersed without agglomeration.

[0082] like Figure 3 As shown, in the FeTe-DAC of this embodiment of the invention, only a broad carbon peak appears, and no other impurity peaks appear, indicating that there are no impurity peaks such as Te compounds or other compounds.

[0083] like Figure 4 As shown, in the FeTe-DAC of this embodiment of the invention, there are abundant isolated iron-tellurium atom pairs (highlighted parts), indicating that the iron-tellurium atom pairs are all atomically dispersed and exist in the form of diatomic atoms.

[0084] like Figure 5 As shown, in the FeTe-DAC embodiment of the present invention, the specific surface area is as high as 920 m². 2 / g.

[0085] like Figure 6 As shown, in the FeTe-DAC of this invention, the N doping types are mainly pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen.

[0086] like Figure 7 As shown, in the FeTe-DAC embodiment of the present invention, the oxidation state of Fe is +3.

[0087] like Figure 8 As shown, in the FeTe-DAC embodiment of the present invention, the oxidation state of Te is +4.

[0088] To evaluate the performance of the FeTe-DAC obtained by the method of this invention, the following tests were performed:

[0089] (1) Electrocatalytic ORR performance test:

[0090] Preparation of catalyst slurry: Weigh 6 mg of FeTe-DAC from this embodiment of the invention, transfer it to a 5 mL centrifuge tube, and then add 5% 40 µL of Nafion membrane solution and 960 µL of isopropanol / water mixed solution (v:v=1:3) dropwise to the centrifuge tube. Sonicate for 1 h to obtain catalyst slurry.

[0091] Electrocatalytic performance testing was conducted in a three-electrode system. 10 µL of catalyst slurry was pipetted onto the surface of a glassy carbon electrode and dried at room temperature to serve as the working electrode; a graphite rod was used as the counter electrode; and a saturated calomel electrode (SCE) was used as the reference electrode. The electrolyte was a 0.1 mol / L KOH solution; the testing environment was room temperature and pressure. Linear sweep voltammetry curves were obtained using a Shanghai Chenhua CHI630E electrochemical workstation.

[0092] The electrochemical testing conditions are as follows: before the electrocatalytic reaction, high-purity oxygen is introduced into the reaction system for 0.5 hours to saturate the oxygen in the reaction system.

[0093] like Figure 9 As shown, in the FeTe-DAC embodiment of this invention, the half-wave potential reaches as high as 0.946V. With increasing rotational speed, the limiting current density also gradually increases. Linear fitting reveals that this process is a typical four-electron process, indicating higher ORR reactivity compared to the noble metal catalyst Pt / C. Because the atomic radius of Te is much larger than that of Fe, the introduction of Te increases the distortion of the iron single-atom local environment, modulates the electronic structure of the material, optimizes the adsorption-desorption process of the reaction intermediates, and thus improves the catalytic performance of the material.

[0094] like Figure 10 As shown, in the FeTe-DAC embodiment of the present invention, the limiting current density gradually increases with the increase of rotational speed. Through linear fitting, it is concluded that this process is a typical four-electron process.

[0095] like Figure 11As shown, the FeTe-DAC of this embodiment of the invention underwent 10,000 cycles of cyclic voltammetry acceleration cycling. Compared with the LSV curve of the first cycle, the half-wave potential showed almost no loss, indicating that the FeTe-DAC of this embodiment of the invention has high electrocatalytic ORR stability.

[0096] (2) Cyclic performance test of quasi-solid-state zinc-air battery:

[0097] Preparation of the air electrode: Weigh 60 mg of FeTe-DAC and 10 mg of acetylene black from this embodiment of the invention and place them in a mortar. Add 1 mL of ethanol and grind to form a mixed slurry. Then, use a pipette to add 40 µL of 60% polytetrafluoroethylene emulsion to the mixed slurry, and add another 1 mL of ethanol. Grind thoroughly to obtain a sheet-like catalyst layer. Fix the nickel foam, the water-proof and breathable membrane, and the catalyst in this order, and press the three together on a roller press to form the air electrode.

[0098] Assembly of the quasi-solid-state zinc-air battery: Following a sandwich structure, the organic gel electrolyte is placed between the zinc negative electrode and the air electrode, and fixed using a special battery clamp to ensure close contact between the gel electrolyte and the zinc negative electrode and the air electrode, thus assembling the quasi-solid-state zinc-air battery. Testing was conducted at room temperature and pressure. The charge-discharge cycle current density was 50 mA·cm⁻¹. -2 .

[0099] like Figure 12 As shown, in this embodiment of the invention, FeTe-DAC and noble metal Pt / C are used at 50 mA·cm⁻¹. -2 The battery charge-discharge cycle performance shows that the discharge performance of noble metal Pt / C begins to decline significantly from the 200th cycle, while the discharge performance of FeTe-DAC begins to decline from the 420th cycle. This indicates that the cycle performance of FeTe-DAC in this embodiment of the invention is higher than that of commercial Pt / C, and it has better charge-discharge cycle performance.

[0100] Example 2

[0101] The only difference between Example 2 and Example 1 is that the temperature of the first heat treatment is 600℃ and the temperature of the second heat treatment is 300℃.

[0102] To evaluate the catalytic performance of FeTe-DAC in the embodiments of the present invention, the following methods were used for testing:

[0103] (1) Electrocatalytic ORR performance test: Same as in Example 1.

[0104] like Figure 13As shown, the half-wave potential of FeTe-DAC in this embodiment of the invention is 0.833V. As the rotation speed increases, the limiting current density also gradually increases. Linear fitting shows that this process is a typical four-electron process, and it has worse ORR reaction activity compared with the noble metal catalyst Pt / C.

[0105] (2) Quasi-solid-state zinc-air battery cycle performance test: Same as Example 1. The FeTe-DAC in Example 2 was tested at 50 mA / cm. -2 Its battery cycle performance is lower than that of commercial Pt / C, exhibiting worse charge-discharge cycle performance.

[0106] Example 3

[0107] The only difference between Example 3 and Example 1 is that the temperature of the first heat treatment is 1000℃ and the temperature of the second heat treatment is 600℃.

[0108] To evaluate the catalytic performance of FeTe-DAC in the embodiments of the present invention, the following methods were used for testing:

[0109] (1) Electrocatalytic ORR performance test: Same as in Example 1.

[0110] like Figure 14 As shown, the half-wave potential of FeTe-DAC in this embodiment of the invention is 0.919V. As the rotation speed increases, the limiting current density also gradually increases. Linear fitting shows that this process is a typical four-electron process, and it has higher ORR reaction activity compared with the noble metal catalyst Pt / C.

[0111] (2) Quasi-solid-state zinc-air battery cycle performance test: Same as Example 1. The FeTe-DAC in Example 2 was tested at 50 mA / cm. -2 Its battery cycle performance is higher than that of commercial Pt / C, with better charge-discharge cycle performance.

[0112] Comparative Example 1

[0113] The only difference between this comparative example and Example 1 is that: in step (1), the mass of iron acetylacetone is 300.0 mg; in step (2), an N-doped carbon polyhedral catalyst loaded with elemental iron and iron carbide is obtained; and steps (3) and (4) are not performed. The rest is the same as in Example 1.

[0114] Upon testing, the carbon polyhedral catalyst loaded with elemental iron and iron carbide obtained by the method of the present invention in Comparative Example 1 was found to contain diffraction peaks of crystalline nano-iron and iron carbide particles.

[0115] To evaluate the performance of the carbon polyhedral catalysts supported on elemental iron and iron carbide obtained in this comparative example, the following tests were conducted:

[0116] (1) Electrocatalytic ORR performance test:

[0117] Same as Example 1.

[0118] Testing revealed that the ORR activity of the carbon polyhedral catalysts supported on elemental iron and iron carbide obtained in this comparative example was significantly lower than that of the FeTe-DAC obtained in Example 1 of this invention and the commercial Pt / C catalyst.

[0119] Testing revealed that after 10,000 cycles of cyclic voltammetry acceleration, the curve shifted significantly to the left, indicating that the ORR stability of the carbon polyhedral catalysts of supported elemental iron and iron carbide obtained in this comparative example was poor.

[0120] (2) Cyclic performance test of quasi-solid-state zinc-air battery:

[0121] Same as Example 1.

[0122] Tests showed that this comparative example was within 50 mA cm⁻¹. -2 The battery charge-discharge cycle performance of this comparative example is significantly worse than that of commercial Pt / C, indicating that the cycle performance of this comparative example is poor.

[0123] In summary, this demonstrates that increasing the loading of iron salts reduces the electrochemical activity of the catalyst.

[0124] Comparative Example 2

[0125] The only difference between this comparative example and Example 1 is that: in step (1), iron acetylacetone is not added; in step (2), an N-doped carbon polyhedral catalyst is obtained; and steps (3) and (4) are not performed. The rest is the same as in Example 1.

[0126] Upon testing, no diffraction peaks of crystalline iron particles were found in the N-doped carbon polyhedral catalyst obtained in the embodiments of the present invention, indicating that it is mainly composed of amorphous carbon.

[0127] To evaluate the performance of the N-doped carbon polyhedral catalyst obtained in this comparative example, the following tests were conducted:

[0128] (1) Electrocatalytic ORR performance test:

[0129] Same as Example 1.

[0130] Testing revealed that after 10,000 cycles of cyclic voltammetry acceleration, the curve shifted significantly to the left, indicating that the ORR stability of the N-doped carbon polyhedral catalyst obtained in this comparative example was poor.

[0131] (2) Cyclic performance test of quasi-solid-state zinc-air battery:

[0132] Same as Example 1.

[0133] Tests showed that this comparative example was within 50 mA cm⁻¹. -2The battery charge-discharge cycle performance of this comparative example is significantly worse than that of commercial Pt / C, indicating that the cycle performance of this comparative example is poor.

[0134] In summary, this demonstrates that the electrochemical performance of Comparative Example 2 is reduced because it lacks iron single atoms.

[0135] Comparative Example 3

[0136] The only difference between this comparative example and Example 1 is that the black powder obtained in step (2) is a carbon polyhedral catalyst loaded with iron single atoms; steps (3) and (4) are not performed. The rest is the same as in Example 1.

[0137] Testing revealed no diffraction peaks of crystalline iron particles in the carbon polyhedral catalyst loaded with iron single atoms.

[0138] To evaluate the performance of the carbon polyhedral catalyst supported on iron single atoms obtained in this comparative example, the following tests were conducted:

[0139] (1) Electrocatalytic ORR performance test:

[0140] Same as Example 1.

[0141] Testing revealed that after 10,000 cycles of cyclic voltammetry acceleration, the curve shifted significantly to the left, indicating that the ORR stability of the N-doped carbon polyhedral catalyst obtained in this comparative example was poor.

[0142] (2) Cyclic performance test of quasi-solid-state zinc-air battery:

[0143] Same as Example 1.

[0144] Tests showed that this comparative example was within 50 mA cm⁻¹. -2 The battery charge-discharge cycle performance is slightly better than that of commercial Pt / C, but worse than that of Example 1, indicating that the cycle performance of this comparative example is insufficient.

[0145] In summary, this indicates that the electrochemical performance was insufficient because Comparative Example 3 did not form an iron-tellurium diatomic pair.

[0146] Comparative Example 4

[0147] The only difference between this comparative example and Example 1 is that the black powder obtained in step (2) is a carbon polyhedral catalyst loaded with iron single atoms; step (5) is not performed. The rest is the same as in Example 1.

[0148] like Figure 15 As shown, the sample obtained in Comparative Example 4 contains abundant Fe-Te coordination bonds, proving that after the second hydrothermal reaction, Te... 2- It reacts with iron single atoms to form Fe-Te coordinate bonds.

[0149] Testing revealed no diffraction peaks of crystalline iron particles in the carbon polyhedral catalyst loaded with iron single atoms.

[0150] Tests revealed no diffraction peaks of metal tellurides or other impurities in the iron-tellurium diatomic catalyst that had not undergone calcination after the hydrothermal reaction.

[0151] To evaluate the performance of the undraught iron-tellurium diatomic catalyst obtained in this comparative example, the following tests were conducted:

[0152] (1) Electrocatalytic ORR performance test:

[0153] Same as Example 1.

[0154] like Figure 16 As shown, the half-wave potential of the sample obtained in Comparative Example 4 is 0.89V, which is worse than that of the FeTeDAC obtained after secondary calcination. After 10,000 cycles of cyclic voltammetry acceleration, the curve shifts significantly to the left, indicating that the ORR stability of the N-doped carbon polyhedral catalyst obtained in this comparative example is poor. This suggests that if only hydrothermal treatment is performed without secondary calcination, the Te... 2- Although it forms weak coordination with bare iron single atoms, due to Te 2- Without coordination with nitrogen-doped carbon (C&N) near the iron single atom, the conductivity is poor, which affects electron transfer during the reaction process and consequently prevents the reaction activity from being improved.

[0155] (2) Cyclic performance test of quasi-solid-state zinc-air battery:

[0156] Same as Example 1.

[0157] Tests showed that this comparative example was within 50 mA cm⁻¹. -2 The battery charge-discharge cycle performance is slightly better than that of commercial Pt / C, but worse than that of Example 1, indicating that the cycle performance of this comparative example is insufficient.

[0158] In summary, this indicates that Comparative Example 4 lacked the calcined hydrothermal iron-tellurium diatomic catalyst, resulting in insufficient electrocatalytic oxygen reduction reaction performance.

Claims

1. A method for preparing a FeTe diatomic catalyst, characterized in that, Includes the following steps: (1) First, iron salt and zinc nitrate are stirred and dissolved in methanol solvent to obtain solution A. Then, N-containing organic ligands are stirred and dissolved in methanol solvent to obtain solution B. After mixing solutions A and B, the mixture is allowed to stand for aging, centrifuged, filtered and washed, and vacuum dried to obtain precursor powder. (2) The precursor powder obtained in step (1) is subjected to a heat treatment under an inert atmosphere to obtain a black powder; the temperature of the heat treatment is 900℃~1000℃. (3) Dissolve a strong reducing agent in deoxygenated ultrapure water until the solution is clear and transparent to obtain solution C. Add elemental tellurium or a salt containing tellurium to solution C and shake until the solution is clear again to obtain precursor solution D. (4) The black powder obtained in step (2) is ultrasonically dispersed in the precursor solution D obtained in step (3), hydrothermally heated, centrifuged, filtered and washed, and the black precipitate is freeze-dried to obtain sample powder; the mass-volume ratio of the black powder to elemental tellurium or salt containing tellurium is 0.1g:1mL~10mL; the molar concentration of elemental tellurium or salt containing tellurium in the precursor solution D is 0.05~0.50mol / L; (5) The sample powder obtained in step (4) is subjected to a second heat treatment under an inert atmosphere to obtain FeTe diatomic catalyst; the temperature of the second heat treatment is 500℃~600℃.

2. The method for preparing a FeTe diatomic catalyst according to claim 1, characterized in that: In step (1), the mass ratio of the iron salt to zinc nitrate is 1:8 to 50; the mass-volume ratio of the sum of the iron salt and zinc nitrate in solution A to the methanol solvent is 1g:20mL to 200mL; the iron salt is one or more of iron carbonyl, iron acetylacetone, iron acetate, iron chloride, or iron nitrate; the mass ratio of zinc nitrate to the nitrogen-containing organic ligand is 1:0.8 to 2.0; the mass-volume ratio of the nitrogen-containing organic ligand to the methanol solvent in solution B is 1g:20mL to 200mL; the nitrogen-containing organic ligand is one or more of dimethylimidazolium, hexamethylenetetramine, or ethylenediaminetetraacetic acid; the stirring and dissolving temperatures are all at room temperature, and the times are all 10 to 30 minutes. In step (3), the elemental tellurium includes tellurium powder, and the salt containing tellurium includes one or more of sodium tellurite and sodium tellurate.

3. The method for preparing a FeTe diatomic catalyst according to claim 1, characterized in that: In step (1), the stirring and mixing temperature is room temperature to 140°C, and the time is 1 to 6 hours; the static aging temperature is room temperature to 140°C, and the time is 6 to 24 hours; the vacuum drying pressure is 0.05 to 0.5 MPa, and the time is 12 to 72 hours.

4. The method for preparing a FeTe diatomic catalyst according to claim 1, characterized in that: In step (2), the heat treatment time is 1 to 6 hours, and the inert atmosphere is a mixture of nitrogen, argon, and a mixture of 5% H2 / 95% N2 or a mixture of 5% H2 / 95% Ar.

5. The method for preparing a FeTe diatomic catalyst according to claim 1, characterized in that: The strong reducing agent is one or more of sodium borohydride or hydrazine hydrate; the deoxygenated ultrapure water is deoxygenated ultrapure water in which oxygen is removed by argon gas.

6. The method for preparing a FeTe diatomic catalyst according to any one of claims 1 to 5, characterized in that: In step (3), the oscillation temperature is 20-40℃ and the oscillation time is 10-30 min; the concentration of the strong reducing agent in solution C is 1-4 mol / L.

7. The method for preparing a FeTe diatomic catalyst according to any one of claims 1 to 5, characterized in that: In step (4), the hydrothermal time is 12h~48h, and the hydrothermal temperature is 160~220℃; the centrifugation speed is 6000~10000r / min, and the centrifugation time is 1.5~5min; the freeze-drying temperature is -10~-30℃, and the time is 12~72h.

8. The method for preparing a FeTe diatomic catalyst according to any one of claims 1 to 5, characterized in that: In step (5), the secondary heat treatment time is 1 to 6 hours, and the inert atmosphere is a mixture of nitrogen, argon, and a mixture of 5% H2 / 95% N2 or a mixture of 5% H2 / 95% Ar.

9. A FeTe diatomic catalyst, characterized in that, It is prepared by the method described in any one of claims 1-8.

10. The application of the FeTe diatomic catalyst as described in claim 9 in ORR catalytic reaction.